Influence of Seasons and Varieties on Vase Life of Gerbera (Gerbera jamesonii Hook.) Cut Flower - Acharya, Anil Kumar; Baral, Dilli Ram; Gautam, Durga Mani; Pun, Umed Kumar (Nepal Journal of Science and Technology, 2011)
Postharvest studies were carried out in three varieties of (Gerbera jamesonii Hook.) cvs. Primrose, Malibu and Sunway to find out the effect of growing seasons (autumn, winter and spring) on the vase life of cut flowers during September 2009 to March 2010. Laboratory experiments were carried out in controlled room having 18±2°C temperature, 68±2% relative humidity and 100 lux light. The study revealed that the longest vase life was noticed in Sunway, followed by Primrose and Malibu. Regarding the season of production, longest vase life (18.37 days) was found in the flowers harvested in winter, followed by spring (14.8 days) and autumn (9.57 days). The interaction effect of season and variety showed that longest vase life (23.2 days) was found in Sunway harvested in winter whereas the shorter vase lives (5.7 and 7.8 days) were in Malibu and Primrose respectively harvested in autumn. Stalk length (57.88 cm) and floral diameter (10.78 cm) were highest in autumn while diameter of the stalk (0.64 cm) was the highest in spring. Sunway had the highest floral and stalk diameters, while the stalk length was longer in Malibu and Primrose. Total water uptake during the vase life was highest in flowers grown in winter (34.9 ml), followed by spring (34.7 ml) and autumn (26.14 ml). Key words: floral diameter; floriculture; postharvest; vase life; water uptake DOI: 10.3126/njst.v11i0.4088 Nepal Journal of Science and Technology 11 (2010) 41-46